Principles of hotel front office operations - Baker, Sue (Cassell,Hospitality Press, 2000)
This fully updated second edition has been revised to include recent developments in the industry and ends with a brand new case study that illustrates and reinforces what has been learnt. There is also a new chapter on yield management. The book includes a wide range of student activities and review questions as well as a glossary. BTEC, HCIMA and undergraduate hospitality management students will find this an indispensable text